Impact of Corporate ESG Performance on Enterprise Value: A Case Study of CATL - Liu Ruiheng (SHS Web of Conferences)
Under the global sustainable development initiative and the “dual carbon” goals, Environmental, Social, and Governance (ESG) performance has emerged as a critical metric for evaluating corporate long-term value. This study examines the impact mechanism of corporate ESG performance on enterprise value through a case analysis of Contemporary Amperex Technology Co., Limited (CATL). By evaluating CATL’s ESG practices across three dimensions—environmental (e.g., green manufacturing, carbon neutrality targets), social (e.g., public welfare initiatives), and governance (e.g., board structure optimization, risk management systems)—and integrating quantitative analyses of financial performance (Tobin’s Q ratio, FC ratio, Z-score) and non-financial performance (technological innovation capabilities), the research reveals that CATL’s ESG efforts have significantly enhanced its enterprise value. Key outcomes include reduced operational costs, strengthened risk resilience, increased ESG-oriented investment attraction, and improved market competitiveness. These findings provide theoretical and practical insights for enterprises to refine ESG strategies and achieve sustainable development and provide more valuable business decisions.